Monitoramento e modelagem hidrológica em pequenas bacias hidrográficas rurais pareadas com produção de grãos e pecuária leiteira - Ebling, Éderson Diniz (2018)
Accelerated sediment production represents one of the biggest problems in the world in terms of water and soil degradation. Studies of hydrological and sedimentological processes in watershed scale represent a resource to identify, understand and propose mitigation strategies of the effects of anthropic actions on the production of sediments. Such studies can be conducted by means of continuous automatic monitoring. Sediment production at the river basin scale includes the stages of disaggregation, transport and deposition. In this sense, modeling tools are increasingly used in environmental studies because they help in understanding the impacts of changes in land use and coverage and in predicting future changes in the environment. The objective of this work was to understand, describe and represent the behavior of the hydrological and sedimentological processes by means of monitoring and modeling with the Limburg Soil Erosion Model (LISEM) in two small paired river basins. The semi-arid basins, called the south basin (0.94 km2) and the north basin (0.66 km2), are located in the municipality of Quinze de Novembro, in the physiographic region of the Southern Plateau of the state of Rio Grande do Sul. Hydrosedimentometric measurements were performed between April 2016 and October 2017 in sections of fluviometric monitoring composed of triangular spillways equipped with rainfall, flow stage and turbidity sensors to quantify the rainfall, flow and concentration of suspended sediments, respectively; and with datalogger and solar panels. Suspension samples (water + sediments) were collected manually during rainfall-sediment events to generate a curve for the estimation of suspended sediment concentration. Events of greater magnitude, above 50 mm, besides presenting a rapid response to rainfall events, were responsible for higher flow volume and sediment concentration. The hysteresis predominated in a clockwise direction, with the occurrence of sediment peaks before hydrograph peak, meaning sediment production and sediment mobilization occur predominantly in drainage networks, furrows close to the main channels or convergence of roads. LISEM satisfactory represented surface runoff in rainfall events of different intensities, occurring during the years 2016 and 2017, in the two hydrographic basins, as analyzed by the Nash and Sutcliffe coefficient (>0.75) and bias percentage (≤25%). Some calibrated parameters were very different from the measured values. The southern basin had lower total sediment yield. The presence of ciliary vegetation along the main drainage network in the southern basin may have influenced the damping effect of the surface runoff, converging the movement of surface water from the sloping areas to the main channel during rainfall events, promoting less sediment transport and mobilization in suspension.